THE ASSISTANCE OF THE BEJI VILLAGE TEMPE SUSTAINABLE PRODUCTION (PROJECT BRIEF) - Mudrifah, Mudrifah (Yayasan Education and Social Center, 2023)
Learning Express (LeX) is a 12-day overseas program that equips students with the Design Thinking mindset in a social innovation context. In this program, students enjoy out-of-textbook experiences such as learning a new language and undergoing a community homestay. Students get to interact and build friendships with youths from Asia and gain a more profound understanding of the issues faced by the overseas community. SP students join the students from the University of Muhammadiyah as Overseas Partner Institutions to co-create purposeful, sustainable, and innovative prototype solutions to real-life issues. They develop an understanding of the issues the overseas community faces in the context of their social, economic, and political culture and analyze these issues from multiple perspectives. Through this program, students can apply their teamwork and communication skills, develop a better understanding of themselves and empathy for the community, realize the positive impact they can make in the lives of a community in need, and attain higher resilience